Simulations and fuzzy systems for resource reallocation. (February 2014) - Muñoz, V; Callero, Y; Aguilar, R M
This paper presents a strategy that combines fuzzy logic and discrete event simulation to address the resource relocation problem. In any system with limited resources, the way in which said resources are distributed influences the quality of the services that can be provided. Making these decisions requires studying the various implications that increasing or distributing the resources has on the system. In this paper, we propose the combined use of simulation and fuzzy logic to determine a proper method for distributing resources. We have used the SIGHOS library to model a case involving a hospital process. The resource reallocation process can be monitored throughout the simulation, allowing for a study of the effects that increasing or distributing the resources has on the system.